(untitled) (The Agriculturists, 2013)
An experiment was conducted to evaluate the nutritive potential of soybean meal and mustard oil cake based diets for rearing of Labeo rohita fingerlings under pond condition at the Bangladesh Agricultural University, Mymonsingh during 2008. Three diets designated as treatments were formulated and fed to the stocked fingerlings. Studies have revealed an increase in final weight, average live weight gain, specific growth rate (SGR), lower food conversion ratio (FCR), protein efficacy ratio (PER) and apparent net protein utilization (ANPU%) and survival of fingerlings fed on diet D3, a soybean meal based diet. Carcass composition also revealed high protein and lipid in fish fed on the diet D3. DOI: http://dx.doi.org/10.3329/agric.v11i1.15244 The Agriculturists 2013; 11(1) 61-66